THE CONCEPT OF EDUCATIONAL GUIDANCE AND COUNSELING IN ISLAM - Nenda Nenda; Saiful Muktiali; Siti Juariah; Rini Setyowati (Jurnal Scientia, 2022)
This study aims to describe how the concept of Islamic guidance and counseling contained in the Luqman surah in verses 12-19 is the approach, principles, and field of service. This research is a type of library research (Library Reseach), using the content analysis method. The results of this study show that in Surah Luqman verses 13-17 there is an al-mauidzah al-hasanah approach (speech in a good and useful way) which is found in verse 13 the key word ya‟izhuhu teaches him wisely, verse 16 the keyword lathif halus which means meek, and verse 17 the keyword bil-ma‟ruufi does good or in a good way and approaches al-hikmah in a wise way. Then there are several principles, firstly the principle of godliness (Islamic counseling services must be based on the provisions of Allah Almighty) there is a key word in verse 13 laa tusyrik billaah, innasy-syirka lazuhulmun‟azhim do not you send Allah, indeed fellowshipping Allah is really a great tyranny, the second there is the principle of lillahi ta‟ala (Islamic guidance and counseling is held solely because of Allah) the key word is in verse 14 ilayyal to Me, the principle of compassion, the principle of example, and the principle of akhlakul karimah. Then there are three areas of Islamic guidance and counseling services, namely firstly aqidah guidance (the field of services that help counselors to develop aqidah to their faith) there is a keyword in verse 13 laa tusyrik billaah do not you fellowship Allah SWT with anything, secondly there is moral guidance (the field of service that helps counselors develop relationships of attitude, good behavior) in verse 14 keywords wa washshoinal-ingsaanabiwaalidaih (we command to man to do good to both his parents), and verse 15 of the keyword wa shoohib- humaa fid-dun-yaa ma‟ruuf (do them in the world well). And the third there is the guidance of worship (developing a relationship to God through charitable worship) found in the 17th verse aqimish-sholaata (perform prayers) and performing amar ma‟ruf and nahi mungkar.